A qualidade do atendimento sob a ótica dos usuáros: um estudo de caso no Hospital Militar de Área de Manaus (HMAM) - Donegá, Mizael Bruno Batista (Brasil, 2025)
This study analyzes user satisfaction regarding the quality of services provided at the Military Area Hospital of Manaus (HMAM). It is a case study with a quantitative approach, using secondary data from the hospital’s database. The sample consists of 89 users who responded to a structured questionnaire with Likert scale questions. The objective of the research is to analyze how users perceive the quality of the services provided at the hospital. The results show that most users are middle-aged individuals who experience difficulties using technologies in the care process. The perception of bureaucracy was moderate, while satisfaction with overall care and the medical team was positive, with ratings mostly between 3 and 5 on the scale. It is concluded that, despite the technological challenges, users are satisfied with the medical care, although bureaucracy and waiting times are aspects to be addressed in future improvements. The study reinforces the importance of humanization in care and technological adaptation to ensure greater patient satisfaction.